Habitat associations of Chihuahua Chub (Gila nigrescens) and Rio Grande Sucker (Pantosteus plebeius) in the Mimbres River, New Mexico - Giulio W. Del Piccolo; Zachary B. Klein; Matthew P. Zeigler (PLoS ONE, 2026)
Fish species in arid regions have suffered from disproportionate declines due to anthropogenic activity. Therefore, many arid-region fishes are species of conservation concern and a primary focus of management agencies. Unfortunately, conservation of many of these species is stymied by a general lack of ecological information such as habitat use. In an effort to improve management of two species of conservation concern, we assessed the seasonal and life-stage specific habitat associations Chihuahua Chub Gila nigrescens and Rio Grande Sucker Pantosteus plebeius in the Mimbres River, New Mexico. Fish assemblage and habitat features were evaluated in the winter, spring, and summer of 2022 and 2023. Due to disparate data sets, habitat associations of Chihuahua Chub were analyzed using an N -mixture model and habitat associations of Rio Grande Sucker were assessed using linear regression. The relative abundance of Chihuahua Chub was associated with deep, structurally-complex pool habitats in reaches with dense riparian vegetation. Adult and subadult Rio Grande Sucker relative abundance was associated with low-velocity habitats. Subadult Rio Grande Sucker were associated with shallower habitat relative to adult conspecifics. Additional habitat restorations will likely benefit Chihuahua Chub and Rio Grande Sucker in the Mimbres River. This study informs the implementation of habitat restoration efforts to improve the conservation of both species across their distributions.